Adherence to Treatment in Allergic Rhinitis During the Pollen Season in Europe: A MASK‐air Study - Sousa‐Pinto, Bernardo; Costa, Elísio M.; Vieira, Rafael José; Pfaar, Oliver; Bedbrook, Anna; Amaral, Rita; Brussino, Luisa; Kvedariene, Violeta; Larenas‐Linnemann, Desiree E.; Iinuma, Tomohisa; Pham‐Thi, Nhân; Regateiro, Frederico S.; et al. (Clinical and experimental allergy, 2025)
ABSTRACT Background Adherence to rhinitis treatment has been insufficiently assessed. We aimed to use data from the MASK‐air mHealth app to assess adherence to oral antihistamines (OAH), intra‐nasal corticosteroids (INCS) or azelastine‐fluticasone in patients with allergic rhinitis. Methods We included regular European MASK‐air users with self‐reported allergic rhinitis and reporting at least 1 day of OAH, INCS or azelastine‐fluticasone. We assessed weeks during which patients answered the MASK‐air questionnaire on all days. We restricted our analyses to data provided between January and June, to encompass the pollen seasons across the different assessed countries. We analysed symptoms using visual analogue scales (VASs) and the combined symptom‐medication score (CSMS), performing stratified analyses by weekly adherence levels. Medication adherence was computed as the proportion of days in which patients reported rhinitis medication use. Sensitivity analyses were performed considering all weeks with at most 1 day of missing data and all months with at most 4 days of missing data. Results We assessed 8212 complete weeks (1361 users). Adherence (use of medication > 80% days) to specific drug classes ranged from 31.7% weeks for azelastine‐fluticasone to 38.5% weeks for OAH. Similar adherence to rhinitis medication was found in users with or without self‐reported asthma, except for INCS (better adherence in asthma patients). VAS and CSMS levels increased from no adherence to full adherence, except for INCS. A higher proportion of days with uncontrolled symptoms was observed in weeks with higher adherence. In full adherence weeks, 41.2% days reported rhinitis co‐medication. The sensitivity analyses displayed similar results. Conclusions A high adherence was found in patients reporting regular use of MASK‐air. Different adherence patterns were found for INCS compared to OAH or azelastine‐fluticasone that are likely to impact guidelines. In a study assessing mobile health data, (i) adherence to rhinitis medication was highest for oral antihistamines and lowest for azelastine‐fluticasone, (ii) in weeks of partial adherence, azelastine‐fluticasone was associated with lower levels of reported rhinitis symptoms than other medication classes.